E-cigarette or vaping product use-associated lung injury (EVALI). A case report of a 19-year-old male in Denmark - Mia Ritzau Ishøj Nielsen; Jens-Ulrik Stæhr Jensen; Pradeesh Sivapalan; Michael Perch; Finn Møller-Pedersen (European Clinical Respiratory Journal)
E-cigarette or vaping product use-associated lung injury (EVALI) is a potentially severe acute interstitial lung disease primarily observed in the United States, with sporadic cases reported in Europe. EVALI, though rare, could be susceptible to under-diagnosis due to limited awareness and diagnostic suspicion. We present a case of a 19-year-old male in Denmark diagnosed with severe EVALI. The patient presented with profound respiratory symptoms necessitating intensive care unit (ICU) admission, subsequent intubation, and eventually initiation of extracorporeal membrane oxygenation (ECMO) support. EVALI should be suspected in users of vaping products, who present with sudden-onset severe respiratory insufficiency, and where other main causes can be excluded.